Influence of Health Education Through Audiovisual on Knowledge and Self Management of Hypertension Elderly in Tondo Kelurahan Mantikulore District - Nuranisa (Journal of Public Health and Pharmacy)
Hypertension is one of the non-communicable diseases (PTM) and also often referred to as the "silent killer" because the character of hypertension does not show clear signs and symptoms. Based on data from Talise Health Center, Talise Health Center covers 4 villages, namely: Talise Village, Tondo Village, Layana Indah Village, and Tanamodindi Village. Tondo Village is one of the areas that contributes to the highest number of elderly hypertension. Tondo Village has never conducted health education through audiovisual for the prevention of hypertension in the elderly. This research  aims to determine the effect of health education through audiovisual on knowledge and self-management of elderly hypertension in the Tondo sub-district, Mantikulore sub-district.This type of research is a quantitative research with a pre-experimental design with the type of one group pre-test post-test design. The population in this study amounted to 32 elderly diagnosed with hypertension who actively participated in health checks at the Tondo Sub-Health Health Center. Determination of the sample in this study was done with thetechnique Total Sampling. The samples taken were 32 elderly people diagnosed with hypertension. Collecting data using a questionnaire that was analyzed by the Wilcoxon signed rank test.  The results of this study indicate that there is an effect of health education through audiovisual on knowledge of the elderly with hypertension in Tondo Village, Mantikulore District as evidenced by statistical tests withvalue p=0.000 < 0.05 and there is an effect of health education through audiovisual on  self-management of elderly hypertension in Tondo Village. Mantikulore District.This study suggests to all health workers to always provide understanding or knowledge to the community intensively about the importance and benefits of providing health education in preventing hypertension.